Are patients with chronic obstructive pulmonary disease at a greater risk for the development of autoimmune thyroiditis as an adverse event of immunotherapy in non-small cell lung cancer treatment? - Andrej Zecevic; Ana Blanka-Protic; Aleksandar Jandric; Tatjana Adzic-Vukicevic; Tatjana Adzic-Vukicevic (Pathology and Oncology Research)
IntroductionImmunotherapy has made a significant improvement in the treatment of patients with non-small cell lung cancer (NSCLC). It has a role in boosting the immune system, so it can fight cancer cells. Sometimes, this mechanism can lead to an overstimulation or misdirection of immune response, so it can act against the body itself. One of the organs most affected by this reaction is the thyroid gland, and there is no definitive explanation of the causes of this adverse event.Material and methodsIn this retrospective observational study, we enrolled 103 patients with NSCLC and high PD-L1 expression (>= 50%) who were treated in our Clinic for pulmonology, University Clinical Center of Serbia, using Pembrolizumab as the first-line therapy.ResultsData analysis showed that 41 (39.81%) of 103 patients in our study had an adverse event of immunotherapy, and 21 of them had autoimmune thyroiditis (20.39%). Of all the patients, 19 of them were treated for chronic obstructive pulmonary disease (COPD) before the onset of Pembrolizumab. During treatment, eight of these patients developed thyroid dysfunction. Patients with COPD were at increased risk of developing autoimmune thyroiditis compared to non-COPD patients (OR 3.9 95% CI 1.135–13.260, p = 0.0227).ConclusionOur study showed that patients dealing with COPD have a 3.9 times greater risk of developing autoimmune thyroiditis as an adverse event during Pembrolizumab treatment compared with patients without COPD.